Directional analysis of sea storms. (1st October 2015) - Laface, V.; Arena, F.; Soares, C. Guedes
Abstract: The paper deals with the directional analysis of sea storms in the Atlantic and Pacific Oceans and in the Mediterranean Sea. The main focus of the work is to investigate the variability of wave directions during sea storms. The analysis is carried out starting from significant wave height and wave direction time series. At the first stage storms are selected from time series without conditions on wave direction. Subsequently the directional analysis of each storm is performed by considering the wave direction associated to each sea state during the storm. A methodology to classify the "directional storms" pertaining to a certain directional sector is proposed. Finally a technique to determine the main directions of occurrence of the strongest sea storms and the appropriate width of sectors for directional analysis is proposed. Results are useful for different kind of applications such as directional long-term predictions for the design process of angle-dependent structures or for wave energy converter devices. highlights: The variability of wave direction during sea storms is investigated. A definition of directional sea storm is introduced. A method to identify the main directional sectors is proposed.